Heat flux effect in ηi- mode driven solitary and shock waves in electron-positron-ion plasma - Zakir, U.; Aziz, K.; Haque, Q.; Murad, A.; Sohail, M. (Kuwait Journal of Science, 2021)
The distinguishing role of ion heat flux on the characteristics of the linear and nonlinear ion temperature gradient ($η_{i}$) driven mode in inhomogeneous electron-positron-ion plasma is presented. Inhomogeneity in density, temperature, and the magnetic field is considered. A modified linear dispersion relation is obtained and its different limiting cases: when $η_{i}\gg 2/3$, $% ω_{D} (\text{gradient in magnetic field})=0$ and $β (\text{density ratio of plasma species})=1$ are discussed. Furthermore, an expression for the anomalous transport coefficient of the present model is obtained. Nonlinear structure solutions in the form of solitons and shocks show that mode dynamics enhance in the presence of ion heat flux in electron-positron-ion plasma. The present study has its importance in energy confinement devices such as tokamak because the heat flux observed experimentally in tokamak plasma is much higher than those described by collisions. Further, it could be useful to understand the nonlinear electrostatic excitations in the interstellar medium.